Awareness of risk of infections to health care professionals and its preventive practices among medical students: a cross-sectional study - Savanthe, Aruna Marati; Savolu, Cynthia Subhaprada (International Journal Of Community Medicine And Public Health, 2018)
Background: Occupational health is a neglected public health issue among healthcare workers in developing countries leading to health care associated infections both to patients and medical students unless infection prevention and control (IPC) measures followed. This study was conducted with an aim to assess the degree of knowledge regarding infection in health care professionals and infection control measures among medical students. Methods: A cross-sectional study was conducted from June 1 to July 31, 2017 on 95 students in the MBBS final year Part I at Kurnool Medical College Kurnool by simple random sampling technique after taking informed consent. A semi structured questionnaire with information regarding their knowledge on risk of infection and infection prevention practices was used. Using SPSS ver. 20, data analysed in proportions and means. Results: Mean age of the study participants was 20.29±0.756 years, 83.2% (n=79) students expressed tuberculosis followed by Hepatitis B infection as the most common infection the medical students are exposed to. 97.9% definitely knew that they contact infections if standard precautions are not followed. Only 51.6% students were aware of all steps of hand wash. 83.2% were already vaccinated to hepatitis B and among vaccinated 73.4% had completed the course fully. Conclusions: Effective infection prevention measures are pivotal in providing high quality health care for patients and a safe working environment for those that work in healthcare settings. Hence infection prevention and control guidelines particularly standard precautions should be incorporated into the curriculum before entering clinical postings.